Two new species of Lamourouxia section Hemispadon (Orobanchaceae) from western Mexico - Francisco-Gutiérrez, Antonio; Ruiz-Sanchez, Eduardo; González, Dolores; Lira-Noriega, Andrés (Phytotaxa, 2022)
After almost 30 years since the last description of a Lamourouxia species, in this paper, two new species are described, illustrated, and compared. The new species are endemic to the states of Durango, Jalisco, Nayarit, and Sinaloa in western and northwestern Mexico, and as several species of the genus, these are of restricted geographic distribution and have scarce representation in biological collections. The new species belong to Lamourouxia section Hemispadon. With these new species Lamourouxia reaches a total of 30 species all occurring in the American continent.